Comparison of colour discrimination and electroretinography in evaluation of visual pathway dysfunction in aretinopathic IDDM patients. Issue 1 (January 1995) - Hardy, K J; Fisher, C; Heath, P; Foster, D H; Scarpello, J H
Abstract : The slow progression of diabetic retinopathy makes it difficult to assess the effects of intervention therapy. There is thus a need for surrogate markers of visual change in diabetes. Colour vision tests and electroretinography (ERG) may be useful in this regard; yet little is known of their relative performance in the assessment of visual dysfunction in diabetes. The aim of the present study was to compare colour discrimination (100 hue test) and ERG indices (oscillatory potentials (OP) and pattern ERG (PERG)) in the evaluation of aretinopathic IDDM patients. Colour discrimination was abnormal in 10 aretinopathic IDDM patients when compared with nine age matched controls; mean square root 100 hue error scores were 10.38 (SD 2.89) versus 4.77 (1.87) respectively, p < 0.01. OP implicit times of the ERG were also abnormal; for example, for right eye, mean OP1 implicit time for diabetics versus OP1 implicit time for controls was 20.1 (2.0) versus 18.6 (1.4) ms, p = 0.03. Comparison of the two techniques suggested that the 100 hue test was more sensitive and more specific than ERG OP implicit times in the detection of diabetic visual dysfunction in these patients.